(3ZQjH GdMOjKs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3jgah Ci jSbW hai cJGH dg (B( (3Udi Gddg Ydjg hSde (B) (3jghO JjeGA (B: (3Ef dge GdPeI hYdjge GdLRjI HdG YOGA s
(3BNQgG (B:s
(3hLGA ai GdMOjK (B: (3Ef GdeSdejf hGdeTQcjf deG GdJbhG ai hbYI fgGhfO ZTjJge QjM bSWdGfjI hgj GdefShHI Edi GdbSWd hgh GdZHGQ BNQ cJGH ZQjH GdMOjK HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3HChdgG Jedc CejQ GdeDefjf jMji Hf efUhQ SfI (B1345(3g`s
(3JeJ ebGHdJgG ai faS SfI GdfSN (B" (3SfI (B2060 " (3ai TgQ LeGOi GdChdis
(3ai Chd GdeNWhWI Cfg (B" (3ZQjH GdMOjK hGddZI (B" (3hbO KHJ eG ai BNQgG hGdeTghQ ef YfhGfg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GddZIs